Real rank estimate by hereditary $C^*$-subalgebras by projections - Sudo, Takahiro (MATHEMATICA SCANDINAVICA, 2007)
In this paper we estimate the real rank of $C^*$-algebras by that of their hereditary $C^*$-subalgebras by projections.